Cytotoxic and antibacterial activity of naturally occurring agglutinin produced from the root of Rhizophora mucronata Poir - J. Rajaselvam; M. R. Basil Rose; U. Elaya Perumal; P. Vijayaraghavan (Natural Product Research, 2026)

Multifrequency Electrical Impedance Myography Enhanced with Machine Learning for Screening Patients with Neuromuscular Disorders - Buket Sonbas-Cobb; Seward B. Rutkove; Baoguo Wei; Sara Robicheau; W. David Arnold; Kaneshia Hives; Amy Bartlett; Peter Riley; Aleah Pagan; Stephen M. Chrzanowski; Basil T. Darras; Stephen J. Kolb (Annals of Biomedical Engineering, 2026)
Purpose We evaluated surface electrical impedance myography (EIM) enhanced with machine learning to serve as a new office-based screening tool for neuromuscular disease Methods EIM of nine muscles was successfully performed in 119 adults and 111 children (approximately half healthy and half diseased) for a total of 3158 individual muscle measurements. Multifrequency data were processed with feature engineering and classification. Nested cross-validation assessed performance, with muscle-based predictions aggregated to participant via majority voting Results Single-feature analyses showed moderate-to-good discrimination (area-under-ROC curve of 0.62–0.73). When multifrequency features were used, participant-based logistic regression and extra trees ensemble models achieved 84% accuracy with 88.1% sensitivity in adults and 93% accuracy and 94.6% sensitivity in children. Beyond classification, regression using EIM predicted muscle strength with R 2 = 0.49, outperforming single-frequency correlations Conclusion These results demonstrate that machine learning-enhanced EIM can successfully distinguish individuals with neuromuscular disease from healthy individuals. Nevertheless, further studies in larger populations of people would help advance this technology to the point that it could serve as a convenient, office-based screening tool for neuromuscular disease.

Assessment of Weathering of Microplastics: A Case Study on River Kadambrayar - Nisha Luckins; Sruthy Robert; Basil M. Binu (Water, Air, & Soil Pollution, 2026)

United States forests are increasingly invaded by problematic non-native plants - Kevin M. Potter; Basil V. Iannone; Kurt H. Riitters; Qinfeng Guo; Karun Pandit; Christopher M. Oswalt (Forest Ecology and Management, 2026)

Effectiveness of image-based classifiers for on-site identification of lichens in reserved forest - Karthikumar Sankar; M. Chengathir Selvi; R. Shyam Kumar; Ponmurugan Karuppiah; Govindasami Periyasami; Perumal Karthikeyan; E. Basil Tamil Selvan (Computers and Electronics in Agriculture, 2025)

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Comparative sustainability assessment of laser powder bed fusion additive manufacturing and conventional machining for Ti-6Al-4V: A multi-criteria decision-making approach - Nasser Rizk; Mohammad Nazzal; Basil M. Darras; Ibrahim Deiab (Journal of Cleaner Production, 2025)

Isolation and Screening of Indigenous Microalgal Strains from Diverse Ecological Niches for Lipid and Pigment Production Relevant to Sustainable Biorefinery Applications - Aravind K. Vijay; Syama Prabha; Said Ali M. Salim; Atheesh O. S.; Basil George (BioEnergy Research, 2025)

Eco-friendly structures for sustainable mangrove restoration - Midhun Mohan; Pandi P. Selvam; Ewane Basil Ewane; Lara G. Moussa; Emma F. Asbridge; Stacey M. Trevathan-Tackett; Peter I. Macreadie; Michael S. Watt; Lucy Gwen Gillis; Francoise Cabada-Blanco; Ian Hendy; Eben North Broadbent; et al. (Science of The Total Environment, 2025)

Durability of reactive powder underwater concrete exposed to saline environment: Shatt Al-Arab, Southern Iraq case study - Doha M. Alsaffar; Basil S. Al-Shathr; Suhair K. Abed (Innovative Infrastructure Solutions, 2025)

Mangrove-based carbon market projects: What stakeholders need to address during pre-feasibility assessment - Ewane Basil Ewane; Pandi P. Selvam; Reem AlMealla; Michael S. Watt; Pavithra S. Pitumpe Arachchige; Barbara Bomfim; Wan Shafrina Wan Mohd Jaafar; Soheil Salehian; Tarig Ali; Nithyanandan Manickam; Meshal M. Abdullah; Sophie Westover; et al. (Journal of Environmental Management, 2025)

Earthworm and enchytraeid indicator taxa of different land-use types identified using soil DNA metabarcoding - Jessica Cuartero; Maria J.I. Briones; Basil M. Rast; Beat Stierli; Claudia Maurer-Troxler; Anna-Sofia Hug; Franco Widmer; Jiří Schlaghamerský; Beat Frey (Applied Soil Ecology, 2025)

Ecotourism and mangrove conservation in Southeast Asia: Current trends and perspectives - Austin Blanton; Ewane Basil Ewane; Freddie McTavish; Michael S. Watt; Kerrylee Rogers; Redeat Daneil; Irene Vizcaino; Ana Novo Gomez; Pavithra S. Pitumpe Arachchige; Shalini A.L. King; G.A. Pabodha Galgamuwa; Martha Lucia Palacios Peñaranda; et al. (Journal of Environmental Management, 2024)

Amsacta moorei entomopoxvirus encodes a protein kinase with dual activity and a broad substrate spectrum including two putative cellular substrates - Hacer Muratoğlu; Remziye Nalcacioglu; Basil M. Arif; Zihni Demirbag (Virus Genes, 2024)

Development and characterization of gelatinized starch doped microcellulose paper from tender coconut (Cocos nucifera L) husk - R. Pandiselvam; M.P. Harikrishnan; Anandu Chandra Khanashyam; M. Basil; M. Anirudh; M.R. Manikantan; Anjineyulu Kothakota (Process Safety and Environmental Protection, 2024)

Reinforced water hyacinth based biodegradable cutlery: Green alternative to single-use plastics - M.P. Harikrishnan; R. Raghunathan; Aswin S. Warrier; M. Basil; Sushanta K. Sahoo; R. Pandiselvam; T. Venkatesh; Saju Pillai; Partha Kundu; Anjineyulu Kothakota (Food Packaging and Shelf Life, 2023)

The neurobiology of the Monarch butterfly compass - M. Jerome Beetz; Basil el Jundi (Current Opinion in Insect Science, 2023)

Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Quasi-static cyclic behavior of precast high-strength concrete tunnel segments reinforced with GFRP bars - Basil Ibrahim; Salaheldin Mousa; Hamdy M. Mohamed; Brahim Benmokrane (Engineering Structures, 2023)

The influence of stimulus history on directional coding in the monarch butterfly brain - M. Jerome Beetz; Basil el Jundi (Journal of Comparative Physiology A, 2023)
The central complex is a brain region in the insect brain that houses a neural network specialized to encode directional information. Directional coding has traditionally been investigated with compass cues that revolve in full rotations and at constant angular velocities around the insect’s head. However, these stimulus conditions do not fully simulate an insect’s sensory perception of compass cues during navigation. In nature, an insect flight is characterized by abrupt changes in moving direction as well as constant changes in velocity. The influence of such varying cue dynamics on compass coding remains unclear. We performed long-term tetrode recordings from the brain of monarch butterflies to study how central complex neurons respond to different stimulus velocities and directions. As these butterflies derive directional information from the sun during migration, we measured the neural response to a virtual sun. The virtual sun was either presented as a spot that appeared at random angular positions or was rotated around the butterfly at different angular velocities and directions. By specifically manipulating the stimulus velocity and trajectory, we dissociated the influence of angular velocity and direction on compass coding. While the angular velocity substantially affected the tuning directedness, the stimulus trajectory influenced the shape of the angular tuning curve. Taken together, our results suggest that the central complex flexibly adjusts its directional coding to the current stimulus dynamics ensuring a precise compass even under highly demanding conditions such as during rapid flight maneuvers.

Mastic (Pistacia lentiscus) gum and oral health: a state-of-the-art review of the literature - Maram Ali M. Alwadi; Amrita Sidhu; Méghit Boumédiène Khaled; Basil H. Aboul-Enein (Journal of Natural Medicines, 2023)

Updating IDF Curves Under Climate Change: Impact on Rainfall-Induced Runoff in Urban Basins - Ioannis M. Kourtis; Ioannis Nalbantis; George Tsakiris; Basil Ε. Psiloglou; Vassilios A. Tsihrintzis (Water Resources Management, 2023)

Global warming potential, water footprint, and energy demand of shared autonomous electric vehicles incorporating circular economy practices - Aser Alaa Ahmed; Mohammad A. Nazzal; Basil M. Darras; I.M. Deiab (Sustainable Production and Consumption, 2023)

The plastisphere microbiome in alpine soils alters the microbial genetic potential for plastic degradation and biogeochemical cycling - Joel Rüthi; Basil M. Rast; Weihong Qi; Carla Perez-Mon; Lucrezia Pardi-Comensoli; Ivano Brunner; Beat Frey (Journal of Hazardous Materials, 2023)

Is sitagliptin effective for SARS-CoV-2 infection: false or true prophecy? - Basil Mohammed Alomair; Hayder M. Al-kuraishy; Ali K. Al-Buhadily; Ali I. Al-Gareeb; Michel De Waard; Engy Elekhnawy; Gaber El-Saber Batiha (Inflammopharmacology, 2022)
Coronavirus disease 2019 (Covid-19) is caused by severe acute respiratory syndrome type 2 (SARS-CoV-2). Covid-19 is characterized by hyperinflammation, oxidative stress, and multi-organ injury (MOI) such as acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Covid-19 is mainly presented with respiratory manifestations; however, extra-pulmonary manifestations may also occur. Extra-pulmonary manifestations of Covid-19 are numerous including: neurological, cardiovascular, renal, endocrine, and hematological complications. Notably, a cluster of differentiation 26 (CD26) or dipeptidyl peptidase-4 (DPP-4) emerged as a new receptor for entry of SARS-CoV-2. Therefore, DPP-4 inhibitors like sitagliptin could be effective in treating Covid-19. Hence, we aimed in the present critical review to assess the potential role of sitagliptin in Covid-19. DPP-4 inhibitors are effective against the increased severity of SARS-CoV-2 infections. Moreover, DPP-4 inhibitors inhibit the interaction between DPP-4 and scaffolding proteins which are essential for endosome formation and replication of SARS-CoV-2. Therefore, sitagliptin through attenuation of the inflammatory signaling pathway and augmentation of stromal-derived factor-1 (SDF-1) may decrease the pathogenesis of SARS-CoV-2 infection and could be a possible therapeutic modality in treating Covid-19 patients. In conclusion, the DPP-4 receptor is regarded as a potential receptor for the binding and entry of SARS-CoV-2. Inhibition of these receptors by the DPP-4 inhibitor, sitagliptin, can reduce the pathogenesis of the infection caused by SARS-CoV-2 and their associated activation of the inflammatory signaling pathways.

Are stormwater detention ponds protecting urban aquatic ecosystems? a case study using depressional wetlands - Kayla M. Hess; James S. Sinclair; Alexander J. Reisinger; Eban Z. Bean; Basil V Iannone III (Urban Ecosystems, 2022)

Tocilizumab Reduces Vasospasms, Neuronal Cell Death, and Microclot Formation in a Rabbit Model of Subarachnoid Hemorrhage - Davide M. Croci; Stefan Wanderer; Fabio Strange; Basil E. Grüter; Sivani Sivanrupan; Lukas Andereggen; Daniela Casoni; Michael von Gunten; Hans Rudolf Widmer; Stefano Di Santo; Javier Fandino; Luigi Mariani; et al. (Translational Stroke Research, 2021)

Follicle inhibition at the primordial stage without increasing apoptosis, with a combination of everolimus, verapamil - Michail Pargianas; Ioannis Kosmas; Kyriaki Papageorgiou; Chrysoula Kitsou; Alexandra Papoudou-Bai; Anna Batistatou; Sofia Markoula; Styliani Salta; Alexandros Dalkalitsis; Stratis Kolibianakis; Basil C. Tarlatzis; Ioannis Georgiou; et al. (Molecular Biology Reports, 2020)

Reconstructing the climatic niche breadth of land use for animal production during the African Holocene - Leanne N. Phelps; Olivier Broennimann; Katie Manning; Adrian Timpson; Hélène Jousse; Gregoire Mariethoz; Damien A. Fordham; Timothy M. Shanahan; Basil A. S. Davis; Antoine Guisan (Global Ecology and Biogeography, 2020)
Aim Domestic animals first appeared in the archaeological record in northern Africa c. 9000 years before present and subsequently spread southwards throughout the continent. This geographic expansion is well studied and can broadly be explained in terms of the movement of pastoralist populations due to climate change. However, no studies have explicitly evaluated changes in the climatic niche of these domesticates. A priori, one cannot assume a relationship between the geographic spread of animal production and changes in climatic niche breadth because their relationship is highly variable. Therefore, we investigated Holocene changes in the climatic niche of domestic animals (animal production) and compared these to changes in the climatic niche of hunted terrestrial ungulates. Location The African continent. Time period 9000–500 BP. Major taxa studied Domestic animals, hunted (wild) terrestrial ungulates. Methods For the first time, we applied methods from environmental niche dynamics to archaeological data to reconstruct and quantify changes in the climatic niche breadth of animal production during the African Holocene. We used faunal remains from archaeological assemblages and associated radiocarbon dates to estimate the proportion of the African climate space used for animal production and hunting at 500‐year intervals. Results We found that the climatic niche of domestic species broadened significantly with the geographic spread, most notably during the termination of the African Humid Period, whilst no such broadening occurred for the climatic niche of hunted species. Main conclusions Our results provide a quantitative measure of the extent to which humans have constructed and adapted the climatic niche of animal production to manage their domestic animals across increasingly diverse ecological conditions. By incorporating ecological analysis into estimations of past land use, our methods have the potential to improve reconstructions of land use change, and to provide a foundation on which further niche construction hypotheses may be tested.

Mobility of electrostatically and sterically stabilized gold nanoparticles (AuNPs) in saturated porous media - Annika S. Fjordbøge; Basil Uthuppu; Mogens H. Jakobsen; Søren V. Fischer; Mette M. Broholm (Environmental Science and Pollution Research, 2019)

Amsacta moorei entomopoxvirus encodes a functional heparin-binding glycosyltransferase (AMV248) - Cihan Inan; Hacer Muratoglu; Basil M. Arif; Zihni Demirbag (Virus Genes, 2018)

Fluorescence Quenching Property of C-Phycocyanin from Spirulina platensis and its Binding Efficacy with Viable Cell Components - Meenakshi B. Paswan; Meghna M. Chudasama; Madhusree Mitra; Khushbu Bhayani; Basil George; Shruti Chatterjee; Sandhya Mishra (Journal of Fluorescence, 2016)

A unified approach for quantifying invasibility and degree of invasion - Qinfeng Guo; Songlin Fei; Jeffrey S. Dukes; Christopher M. Oswalt; Basil V. Iannone III; Kevin M. Potter (Ecology, 2015)
Habitat invasibility is a central focus of invasion biology, with implications for basic ecological patterns and processes and for effective invasion management. “Invasibility” is, however, one of the most elusive metrics and misused terms in ecology. Empirical studies and meta‐analyses of invasibility have produced inconsistent and even conflicting results. This lack of consistency, and subsequent difficulty in making broad cross‐habitat comparisons, stem in part from (1) the indiscriminant use of a closely related, but fundamentally different concept, that of degree of invasion (DI) or level of invasion; and (2) the lack of common invasibility metrics, as illustrated by our review of all invasibility‐related papers published in 2013. To facilitate both cross‐habitat comparison and more robust ecological generalizations, we clarify the definitions of invasibility and DI, and for the first time propose a common metric for quantifying invasibility based on a habitat's resource availability as inferred from relative resident species richness and biomass. We demonstrate the feasibility of our metric using empirical data collected from 2475 plots from three forest ecosystems in the eastern United States. We also propose a similar metric for DI. Our unified, resource‐based metrics are scaled from 0 to 1, facilitating cross‐habitat comparisons. Our proposed metrics clearly distinguish invasibility and DI from each other, which will help to (1) advance invasion ecology by allowing more robust testing of generalizations and (2) facilitate more effective invasive species control and management.

Bio-optic characterization of Discosphaera tubifer bloom occurs in an overcrowded fishing harbour at Veraval, India - Subir Kumar Mandal; Vipul R. Patel; Ganesh Temkar; Basil M. George; Mini Raman (Environmental Monitoring and Assessment, 2015)

The age and post-glacial development of the modern European vegetation: a plant functional approach based on pollen data - Basil A. S. Davis; Pamela M. Collins; Jed O. Kaplan (Vegetation History and Archaeobotany, 2015)

Remote sensing- and GIS-based runoff modeling with the effect of land-use changes (a case study of Cochin corporation) - M. Nagarajan; George Basil (Natural Hazards, 2014)

Northward migration under a changing climate: a case study of blackgum (Nyssa sylvatica) - Johanna Desprez; Basil V. Iannone; Peilin Yang; Christopher M. Oswalt; Songlin Fei (Climatic Change, 2014)

Neuroimaging Endophenotypes in Animal Models of Autism Spectrum Disorders: Lost or Found in Translation? - Marija M. Petrinovic; Basil Künnecke (Psychopharmacology, 2014)

Towards mapping the late Quaternary vegetation change of Europe - Thomas Giesecke; Basil Davis; Simon Brewer; Walter Finsinger; Steffen Wolters; Maarten Blaauw; Jacques-Louis de Beaulieu; Heather Binney; Ralph M. Fyfe; Marie-José Gaillard; Graciela Gil-Romera; W. O. van der Knaap; et al. (Vegetation History and Archaeobotany, 2014)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

The mid‐Holocene vegetation of the Mediterranean region and southern Europe, and comparison with the present day - Pamela M. Collins; Basil A. S. Davis; Jed O. Kaplan (Journal of Biogeography, 2012)
Aim To contribute to the intense debate surrounding the relative influence of climate and humans on Mediterranean‐region land cover over the past 6000 years, we assess the Holocene biogeography and vegetation history of southern Europe by means of an extensive pollen record dataset. Location The Mediterranean biogeographical zone and neighbouring parts of Iberia, the Alps and Anatolia, between 30° N, 48° N, 10° W and 45° E. Methods We compiled a southern European pollen record dataset using available pollen databases (124 sites) and other sources (74 sites), with improved spatial coverage and dating control compared with earlier studies. We used only those sites that had pollen data for both 0 ka and 6 ka. We reconstructed mid‐Holocene and present‐day biomes, arboreal pollen percentages and distribution and relative abundance of 11 key woody taxa, with anomaly maps. Results Northern temperate forest biomes extended further south at the mid‐Holocene than at present, but not as far as earlier studies suggested. Sclerophyllous vegetation occurred along the Mediterranean coast throughout the region at 6 ka. Arboreal pollen percentages were up to 50% higher than at present. At 6 ka, Olea , Fagus and Juniperus had smaller distributions and/or abundances; Abies , Cedrus and both deciduous and evergreen Quercus had larger distributions and/or abundances; Phillyrea , Pistacia and Cistus showed minimal difference; and Pinus showed a cosmopolitan distribution with variable abundance. Main conclusions Temporal difference analysis is more meaningful when only sites containing samples for all time slices are analysed. During the mid‐Holocene, southern Europe was more heavily forested with temperate vegetation than it is at present, but drought‐tolerant xeric vegetation was still widespread along the southern margins of the region. Although human land use may have caused the degradation of land between the mid‐Holocene and the present, the mere presence of xeric vegetation in the Mediterranean region does not require human impact. This challenges the commonly held belief that modern Mediterranean vegetation represents a ‘degraded’ state.

Erratum to: Differential expression of stem cell markers in human follicular bulge and interfollicular epidermal compartments - Shu Jiang; Longmei Zhao; Bhamini Purandare; Basil M. Hantash (Histochemistry and Cell Biology, 2010)

Differential expression of stem cell markers in human follicular bulge and interfollicular epidermal compartments - Shu Jiang; Longmei Zhao; Bhamini Purandare; Basil M. Hantash (Histochemistry and Cell Biology, 2010)

The Role of Posture, Magnification, and Grip Force on Microscopic Accuracy - Basil Safwat; Eileen L. M. Su; Roger Gassert; Chee Leong Teo; Etienne Burdet (Annals of Biomedical Engineering, 2009)

Maturity-associated variation in the growth and functional capacities of youth football (soccer) players 13?15years - Robert M. Malina; Joey C. Eisenmann; Sean P. Cumming; Basil Ribeiro; Joo Aroso (European Journal of Applied Physiology, 2004)

Nucleotide Sequence and Transcriptional Analysis of a Putative Basic DNA-Binding Protein of Helicoverpa armigera Nucleopolyhedrovirus - Hualin Wang; Xinwen Chen; Hanzhong Wang; Basil M. Arif; Just M. Vlak; Zhihong Hu (Virus Genes, 2001)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Geographical and vertical variation of the earth's seismicity - Theodoros M. Tsapanos; Basil C. Papazachos (Journal of Seismology, 1998)

The East Auckland Current, 1994–95 - Basil R. Stanton; Philip J. H. Sutton; Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 1997)
The East Auckland Current (EAUC) was investigated in 1994–95 using data from three CTD surveys (conductivity, temperature, depth) and moored current meters. The strength and position of the EAUC was found to be highly variable with most of the current re‐circulating around an anticyclonic eddy north‐east of North Cape—the North Cape Eddy. The position and intensity of this eddy changed resulting in complex flow patterns with a south‐east flowing EAUC not always present as a contiguous feature. The current meter data showed a high level of mesoscale variability with low spatial coherence, suggesting that the along shore correlation length scale was c. 100 km in this current system. Near North Cape, a persistent but variable counter‐current was found inshore of the EAUC. To the south‐east a permanent anticyclonic East Cape Eddy found north of East Cape appears to dominate the flow field and the genesis of the East Cape Current.

Experiments with colchicine treatment of potatoes in Alaska - Basil M. Bensin (American Journal of Potato Research, 1952)